PENDEKATAN INTERDISIPLINER DAN MULTIDISIPLINER SEBAGAI STRATEGI PENGUATAN DAKWAH BERBASIS MASYARAKAT - Salman Alfarisi; Endah Kurniati; Robin; Nasor (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2025)
Community based da’wah in the contemporary era faces complex challenges that demand innovation in both strategy and approach. This study aims to analyze the application of interdisciplinary and multidisciplinary approaches as strategies for strengthening da’wah that are relevant to modern social dynamics. The interdisciplinary approach allows for the integration of Islamic sciences with various fields such as education, communication, sociology, and information technology, making da’wah not only normative but also solution-oriented in addressing societal issues. Meanwhile, the multidisciplinary approach enhances cross-disciplinary collaboration to produce da’wah strategies that are adaptive, participatory, and sustainable. This study employs a descriptive qualitative method with a library research approach, examining literature related to the development of da’wah methodologies and the integration of knowledge. The findings show that the implementation of both approaches can increase the effectiveness of da’wah in empowering communities, strengthening social cohesion, and building contextual and inclusive religious awareness. Thus, the synergy among various disciplines becomes a strategic foundation for strengthening community-based da’wah amid the current wave of global change.